Pengaruh Pandemi Covid-19 Terhadap Masalah Kesehatan Mental yang Muncul Pada Anak dan Remaja - Arief Agus Triansyah; Azilla Aoranti Anugrah; Depa Iwa Hermansah; Lifia Ayu Marisa; Kurniawan Arip Alpa Rizki; Raisya Selviana; Sandy Sukmaya (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Adolescence is a time of transition from childhood to maturity, and as such, it requires self-control and psychological care because it is undoubtedly going through a process of self-discovery. Routine, education, leisure, and worry are all impacted by the COVID-19 pandemic, which impacts children's and adolescents' mental and psychological health. We used secondary data to investigate how the COVID-19 pandemic has affected children's and teenagers' mental health. 1182 people from different educational institutions in Delhi-NCR, ranging in age. Additionally, a survey of 56 US states was conducted. The paper used associative research techniques to determine how the COVID-19 pandemic affected various age groups' performance on online tests, health problems during social separation, and stress management. The survey's findings also revealed a yearly percentage increase in the difficulty of focusing, remembering, and making judgments in 56 US states using correlation and basic linear regression analysis. Better educational advice is needed for adolescents, as this is thought to have an impact on their mental health.